Economic and nutritional implications of losses and contributing factors along the bean value chain. (May 2020) - Ellis, E.; Kwofie, E.M.; Ngadi, M.
Abstract: The contribution of food availability to food insecurity and poverty reduction, makes food loss an important issue. The study provides findings on the economic and nutritional implications of produce loss at different stages of the common bean value chain and discuss farmers role in reducing losses through their measurement of loss and awareness of loss factors. Average losses at the postharvest handling stage, storage and marketing stage were estimated to be 85.6%, 11.6% and 2.8% of the total loss along the chain respectively. The analysis was extended to determining the economic and nutrient losses along the value chain. Losses contributes to economic losses of $269, 417.6 and $8, 035.2 at the production and marketing stages respectively. The true cost based on value added loss estimations was however found to be $423, 737.8 at the production stage. Findings revealed that out of the total nutrients lost at the post harvest handling stage contributes (88.07%) contributes to majority of the losses compared to the storage stage (11.93%). Losses were found to be caused by unfavourable weather, seed quality, insects, diseases and inefficient handling practices. More than 60% of both producers and traders measured their losses and had a fair understanding of the factors causing losses with a significant difference being observed between measurers and non-measurers. Lack of awareness was not found to be a contributing factor to losses but inability to manage them. Improvement in the capacity of agents to better manage losses is expected to result in lower levels of losses. Highlights : Postharvest handling and storage contribute 85.65% and 11.60% to the total weight loss along the common bean chain. . The true economic cost based on value added loss estimations was found to be $423, 737.8 at the production stage. Post-harvest handling contributes up to 88% of total nutrient losses along the value chain. Non-measurers had significantly more positive responses on the factors influencing losses compared to measurers. A strong level of agreement was not observed for the awareness of physical losses translating into nutrient losses.